2011
DOI: 10.3390/ijms12063409
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Expression and Clinical Significances of Lewis y Antigen and Integrin αv, β3 in Epithelial Ovarian Tumors

Abstract: ObjectiveTo detect the expression and clinical significances of Lewis y antigen and integrin αv, β3 in epithelial ovarian tumors, and to explore the expression correlation between Lewis y antigen and integrin αv, β3.MethodsImmunohistochemical staining was performed in 95 cases of epithelial ovarian cancer, 37 cases of borderline tumors, 20 cases of benign tumors, and 20 cases of normal ovarian tissue, for the detection of Lewis y antigen and integrin αv, β3 expressions, and to analyze the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…αvβ3 is highly expressed by different ovarian cancer cell lines 9,11 and by primary tissue samples from ovarian cancer patients, 12,13 correlating with disease prognosis. 8,15 Moreover, independently of the αvβ3 expression in the primary tumor, a recent report indicated that the overwhelming majority of tumor vessels in ovarian carcinomas express this receptor, 12 signifying relevance to anti-angiogenic therapeutic strategies. The targeting of αvβ3 in ovarian cancer has been emphasized in mouse models, wherein αvβ3 inhibition improved survival 11,50-53 and the response to therapy correlated with αvβ3 expression level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…αvβ3 is highly expressed by different ovarian cancer cell lines 9,11 and by primary tissue samples from ovarian cancer patients, 12,13 correlating with disease prognosis. 8,15 Moreover, independently of the αvβ3 expression in the primary tumor, a recent report indicated that the overwhelming majority of tumor vessels in ovarian carcinomas express this receptor, 12 signifying relevance to anti-angiogenic therapeutic strategies. The targeting of αvβ3 in ovarian cancer has been emphasized in mouse models, wherein αvβ3 inhibition improved survival 11,50-53 and the response to therapy correlated with αvβ3 expression level.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 A correlation between the expression of αvβ3 and ovarian tumor progression has been reported. 8,14,15 Independently of the αvβ3 expression in the primary tumor, the overwhelming majority of tumor vessels in ovarian carcinomas express this receptor. 12 Besides its function in ovarian cancer metastasis, αvβ3 has been reported to have a role in ovarian tumor growth in vivo 11 and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of integrin αvβ3 expression has been shown to link with disease prognosis [27, 31]. In addition, there is overexpression of αvβ3 in blood vessels supporting ovarian carcinomas [29], suggesting integrin αvβ3 contributes to angiogenesis and metastasis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that carbohydrate antigens on the cell surface are closely related to integrins. In our previous work, we have found that as a part of the integrin αvβ3 structure, Lewis y antigen expression is related to the degree of invasiveness of ovarian cancer [6]. Here we use immunohistochemistry to further study the expression of Lewis y antigen and integrin αvβ3 in tissue specimens from patients with chemotherapy resistant or sensitive ovarian cancer and analyze how the expression of these molecules correlates with chemotherapy resistance and the resulting clinical significance.…”
Section: Introductionmentioning
confidence: 99%